Innovative firms’ internationalization and decision-making logics: Insights from French firms - Godek-Brunel, Magdalena; Triki, Dora (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2025)
The internationalization processes of innovative firms, employing distinct decision-making logics, differ from those of traditional companies in mature industries. Although recent studies have examined these approaches, our understanding of the decision-making logics specific to innovative firms throughout the internationalization process remains limited. Drawing on Sarasvathy’s (2001) causation and effectuation approach, we conducted a longitudinal study of the decision-making logics of five French innovative firms at different stages of their internationalization. Our results show that managers’ decision-making logics may shift multiple times throughout the internationalization process depending on the context and resources. This study contributes to the literature by elucidating the evolution of decision-making logic over time, particularly when firms are selecting their target market and subsequently entering that market.